Dihydroartemisinin-piperaquine failure associated with a triple mutant including kelch13 C580Y in Cambodia: an observational cohort study. Issue 6 (June 2015) - Spring, Michele D; Lin, Jessica T; Manning, Jessica E; Vanachayangkul, Pattaraporn; Somethy, Sok; Bun, Rathvicheth; Se, Youry; Chann, Soklyda; Ittiverakul, Mali; Sia-ngam, Piyaporn; Kuntawunginn, Worachet; Arsanok, Montri; et al.
Summary Background Dihydroartemisinin-piperaquine has been adopted as first-line artemisinin combination therapy (ACT) for multidrug-resistant Plasmodium falciparum malaria in Cambodia because of few remaining alternatives. We aimed to assess the efficacy of standard 3 day dihydroartemisinin-piperaquine treatment of uncomplicated P falciparum malaria, with and without the addition of primaquine, focusing on the factors involved in drug resistance. Methods In this observational cohort study, we assessed 107 adults aged 18–65 years presenting to Anlong Veng District Hospital, Oddar Meanchey Province, Cambodia, with uncomplicated P falciparum or mixed P falciparum/Plasmodium vivax infection of between 1000 and 200 000 parasites per μL of blood, and participating in a randomised clinical trial in which all had received dihydroartemisinin-piperaquine for 3 days, after which they had been randomly allocated to receive either primaquine or no primaquine. The trial was halted early due to poor dihydroartemisinin-piperaquine efficacy, and we assessed day 42 PCR-corrected therapeutic efficacy (proportion of patients with recurrence at 42 days) and evidence of drug resistance from the initial cohort. We did analyses on both the intention to treat (ITT), modified ITT (withdrawals, losses to follow-up, and those with secondary outcomes [eg, new non-recrudescent malaria infection] were censored on the last day of follow-up), and per-protocol populations of the original trial. The original trial was registered with ClinicalTrials.gov, number NCT01280162. Findings Between Dec 10, 2012, and Feb 18, 2014, we had enrolled 107 patients in the original trial. Enrolment was voluntarily halted on Feb 16, 2014, before reaching planned enrolment (n=150) because of poor efficacy. We had randomly allocated 50 patients to primaquine and 51 patients to no primaquine groups. PCR-adjusted Kaplan-Meier risk of P falciparum 42 day recrudescence was 54% (95% CI 45–63) in the modified ITT analysis population. We found two kelch13 propeller gene mutations associated with artemisinin resistance—a non-synonymous Cys580Tyr substitution in 70 (65%) of 107 participants, an Arg539Thr substitution in 33 (31%), and a wild-type parasite in four (4%). Unlike Arg539Thr, Cys580Tyr was accompanied by two other mutations associated with extended parasite clearance (MAL10:688956 and MAL13:1718319). This combination triple mutation was associated with a 5·4 times greater risk of treatment failure (hazard ratio 5·4 [95% CI 2·4–12]; p<0·0001) and higher piperaquine 50% inhibitory concentration (triple mutant 34 nM [28–41]; non-triple mutant 24 nM [1–27]; p=0·003) than other infections had. The drug was well tolerated, with gastrointestinal symptoms being the most common complaints. Interpretation The dramatic decline in efficacy of dihydroartemisinin-piperaquine compared with what was observed in a study at the same location in 2010 was strongly associated with a new triple mutation including the kelch13 Cys580Tyr substitution. 3 days of artemisinin as part of an artemisinin combination therapy regimen might be insufficient. Strict regulation and monitoring of antimalarial use, along with non-pharmacological approaches to malaria resistance containment, must be integral parts of the public health response to rapidly accelerating drug resistance in the region. Funding Armed Forces Health Surveillance Center/Global Emerging Infections Surveillance and Response System, Military Infectious Disease Research Program, National Institute of Allergy and Infectious Diseases, and American Society of Tropical Medicine and Hygiene/Burroughs Wellcome Fund.